2008
DOI: 10.1590/s1135-57272008000600002
|View full text |Cite
|
Sign up to set email alerts
|

Guía europea de prevención cardiovascular en la práctica clínica: Adaptación española del CEIPC 2008

Abstract: We present the Spanish adaptation from the CEIPC of the European Guidelines on Cardiovascular Disease Prevention in Clinical Practice 2008. This guide recommends the SCORE model for risk evaluation. The aim is to prevent premature mortality and morbidity due to CVD by means of dealing with its related risk factors in clinical practice. The guide focuses on primary prevention and emphasizes the role of the nurses and primary care medical doctors in promoting a healthy life style, based on increasing physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
17

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 79 publications
(1 reference statement)
0
8
0
17
Order By: Relevance
“…The CEIPC is an official alliance of 15 professional scientific societies supported by the Spanish Ministry of Health. Two national adaptations of the European guidelines for CVD prevention have been developed by CEIPC, the first in 2004 [2] and the second in 2008 [3]. These adaptations have introduced some changes with regard to treatment targets and implementation in order to reflect different social and medical circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The CEIPC is an official alliance of 15 professional scientific societies supported by the Spanish Ministry of Health. Two national adaptations of the European guidelines for CVD prevention have been developed by CEIPC, the first in 2004 [2] and the second in 2008 [3]. These adaptations have introduced some changes with regard to treatment targets and implementation in order to reflect different social and medical circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Study subjects were over 18 years of age, with high CVR and confirmed hypercholesterolaemia, in other words, total cholesterol (TC) > 5.17 mmol/l or LDL-C > 3.36 mmol/l, or patients taking statins or other lipid-lowering drugs. High CVR was defined as a SCORE risk ≥ 5% or the presence of diabetes (type 2 or type 1 with microalbuminuria), or the presence of severe hyperlipidaemia (TC ≥ 8.28 mmol/l or LDL-C ≥ 6.21 mmol/l measured at the time of the visit), or severe hypertension (180/110 mmHg), following the recommendations in force in Spain (18).…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol control targets were established at each visit based on documented LDL-C levels and CEIPC 2008 guidelines (18). These targets were to reduce LDL-C < 2.59 mmol/l in patients with type 2 or type 1 diabetes or severe hyperlipidaemia and < 3.36 mmol/l in patients with none of the foregoing conditions.…”
Section: Statisticsmentioning
confidence: 99%
“…The main difference between the SCORE risk chart and the Framingham model is that it estimates the risk for all atherothrombotic cardiovascular manifestations, including stroke, heart failure, peripheral arterial insufficiency or certain aneurysms, and not just CHD. The SCORE charts are currently the CVD charts recommended by the European Societies [44] and the Spanish Interdisciplinary Committee for Cardiovascular Disease Prevention (CEIPC) [45]. The SCORE risk charts calibrated for Spain will be used [46].…”
Section: Methodsmentioning
confidence: 99%